Should patients with Phosphomannomutase 2-CDG (PMM2-CDG) be screened for adrenal insufficiency? - Čechová, Anna; Honzík, Tomáš; Edmondson, Andrew C; Ficicioglu, Can; Serrano, Mercedes; Barone, Rita; De Lonlay, Pascale; Schiff, Manuel; Witters, Peter; Lam, Christina; Patterson, Marc; Janssen, Mirian C H; et al. (Molecular genetics and metabolism, 2021)
PMM2-CDG is the most common congenital disorder of glycosylation (CDG) accounting for almost 65% of known CDG cases affecting N-glycosylation. Abnormalities in N-glycosylation could have a negative impact on many endocrine axes. There is very little known on the effect of impaired N-glycosylation on the hypothalamic-pituitary-adrenal axis function and whether CDG patients are at risk of secondary adrenal insufficiency and decreased adrenal cortisol production. Cortisol and ACTH concentrations were simultaneously measured between 7:44 am to 1 pm in forty-three subjects (20 female, median age 12.8 years, range 0.1 to 48.6 years) participating in an ongoing international, multi-center Natural History study for PMM2-CDG (ClinicalTrials.gov Identifier: NCT03173300). Of the 43 subjects, 11 (25.6%) had cortisol below 5 μg/dl and low to normal ACTH levels, suggestive of secondary adrenal insufficiency. Two of the 11 subjects have confirmed central adrenal insufficiency and are on hydrocortisone replacement and/or stress dosing during illness; 3 had normal and 1 had subnormal cortisol response to ACTH low-dose stimulation test but has not yet been started on therapy; the remaining 5 have upcoming stimulation testing planned. Our findings suggest that patients with PMM2-CDG may be at risk for adrenal insufficiency. Monitoring of morning cortisol and ACTH levels should be part of the standard care in patients with PMM2-CDG.
Keywords: vrozené poruchy glykosylace; Phosphotransferases (Phosphomutases); Adrenal Insufficiency; Infant; Humans; kojenec; lidé středního věku; dítě; CDG; Inborn errors of metabolism; Child; Phosphomannomutase 2-CDG; Female; rizikové faktory; mladý dospělý; dospělí; lidé; fosfotransferasy (fosfomutasy); předškolní dítě; Adult; systém hypofýza - nadledviny; Congenital Disorders of Glycosylation; ženské pohlaví; glykosylace; Male; Pituitary-Adrenal System; Middle Aged; ACTH; Adolescent; Cortisol; adrenální insuficience; Young Adult; mužské pohlaví; prospektivní studie; Child, Preschool; Glycosylation; PMM2-CDG; mladiství; Risk Factors; Prospective Studies